2013
DOI: 10.11648/j.ajpc.20130203.11
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemistry of Heteroatomic Compounds: Analysis and Calculation of Thermodynamic Functions of Organometallic Compounds of I-IV Groups of Mendeleev′s Periodic Table

Abstract: It is necessary to note, that the heat of vaporization, all thermodynamic functionscond and heat capacity (C p ) of organometallic compounds of I-IV groups of Mendeleev′s Periodic Table can be well characterized with the number of valence electrons N of them. It is difficult to do some conclusions relatively stoichiometric coefficients i and f in modified by us Kharasch equation ∆ vap,c,f,s Ψ o = i ± f *N as they concern to organometallic compounds of the different groups. Such conclusion can be made on settle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 71 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…The analysis of the results of Table 3 shows that all atomizations of all chosen thermodynamic functions (values of heat capacities were not considered) of different alkanes are depended from the number of valence electrons (Eqs. 4-8; there is bad correlation between ∆ a G o cond and N, r 0.763), as it was shown earlier for the organic molecules [3][4][5][6][7].…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The analysis of the results of Table 3 shows that all atomizations of all chosen thermodynamic functions (values of heat capacities were not considered) of different alkanes are depended from the number of valence electrons (Eqs. 4-8; there is bad correlation between ∆ a G o cond and N, r 0.763), as it was shown earlier for the organic molecules [3][4][5][6][7].…”
Section: Resultsmentioning
confidence: 73%
“…Also it has been found that all functions depend from the number of valence electrons N without of the number (h) of lone electron pairs (g) of all investigated molecules (Eq. 2) Mendeleev′s Periodic [3][4][5][6][7] ∆ g,f,s Ψ o = i ± f *(N -hg) (2) here i and f are stoichiometric coefficients Also we have become interested not only the heat of formation of simple atoms in gaseous and condensed states, but and their other thermodynamic functions, which are known in the literature and summed in Table 1 [8,9].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…-The most significant conclusion is the successful application of the equation (1) for an estimation of the interrelation of all functions with a number of valence electrons without taking into account of lone electrons pairs.…”
Section: Resultsmentioning
confidence: 99%
“…In the present communication we continue to analyze and calculate the changes of thermodynamic functions ∆Ψ o (∆G o , ∆H o , ∆S o ), characterizing the processes of vaporization, combustion and formation of the condensed and gaseous organic compounds and their heat capacities (C p ) of V-VII groups of Mendeleev′s Periodic Table. Previously we have repeatedly shown, that not only the heat of combustion of organometallic compounds of I-IV groups of Periodic Table [1], organic [2,3] and biochemical compounds, such as different carbohydrates [4] and amino acids [5] in the dependence from the number of their valence electrons N are.…”
Section: Introductionmentioning
confidence: 99%